2016
DOI: 10.1021/acs.jctc.6b00128
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Evaluation of Ion Conductivity of the Gramicidin A Channel Using a Polarizable Force Field without Any Corrections

Abstract: Classical molecular dynamic (MD) simulation of membrane proteins faces significant challenges in accurately reproducing and predicting experimental observables such as ion conductance and permeability due to its incapability of precisely describing the electronic interactions in heterogeneous systems. In this work, the free energy profiles of K(+) and Na(+) permeating through the gramicidin A channel are characterized by using the AMOEBA polarizable force field with a total sampling time of 1 μs. Our results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 84 publications
9
69
1
Order By: Relevance
“…; Peng et al . ), demonstrating reduced free energy barriers and thus providing more accurate channel conductance. And, fully polarizable MD simulations were reported recently for other ion channels as well (Dhakshnamoorthy et al .…”
Section: Introductionmentioning
confidence: 99%
“…; Peng et al . ), demonstrating reduced free energy barriers and thus providing more accurate channel conductance. And, fully polarizable MD simulations were reported recently for other ion channels as well (Dhakshnamoorthy et al .…”
Section: Introductionmentioning
confidence: 99%
“…We note that for the H2H conformation, larger values have also been computed, ranging from 12 kcal mol –1 for K + to 15 kcal mol –1 for Na + transfer . A considerable reduction of the computed barrier by using a polarizable force field (Amoeba vs. Charmm) has been reported by Peng et al Differences in the free energies between ions localized in the protein channel and solvated in bulk water have been addressed by Giorgino and De Fabritiis and De Fabritiis et al by steered MD. The authors arrive at 14 and 19 kcal mol –1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In an unpublished work of our lab, parameters for POPC were proposed. And we have reported that the free energy profiles of K + and Na + permeating through the gramicidin A channel embedded in DMPC are characterized by using the AMOEBA polarizable force field …”
Section: Induced Dipole Modelmentioning
confidence: 99%
“…Polarization may contribute 10–20% of the total interaction energy, and if the system is charged, which means polarization and electrostatic are critical, the contribution may increase to 40% . The AMOEBA POPC and DMPC force field have been constructed in 2016, and the PMF results of Na + and K + pass through gA channel show that the parameters of lipid are reliable, and the enhanced sampling algorithms based on AMOEBA has been implemented in the OpenMM . In these cases, the polarizable force fields can further promote the accuracy of the binding free energy of membrane protein with the ligand to achieve near‐quantitative agreement with experimental binding free energy values .…”
Section: Applications Of Polarizable Force Fieldmentioning
confidence: 99%